New Potential Weapons for Refractory Scleritis in the Era of Targeted Therapy - Claudia Fabiani; Jurgen Sota; Maite Sainz-; Laura Pelegrín; Giacomo Emmi; Giuseppe Lopalco; Florenzo Iannone; Lorenzo Vannozzi; Silvana Guerriero; Maria Chiara Gelmi; Donato Rigante; Gian Marco Tosi; et al. (Hindawi Limited, 2020)
Objective. To assess the efficacy of biologic drugs, beyond tumor necrosis factor- (TNF-) α inhibitors, in the management of noninfectious refractory scleritis, either idiopathic or associated with systemic immune-mediated disorders. Patients and Methods. This is a retrospective study assessing the efficacy of several biologic agents (rituximab, anakinra, tocilizumab, and abatacept) and the small molecule tofacitinib in the treatment of scleritis through assessment of scleral inflammation and relapses, as well as treatment impact on best-corrected visual acuity (BCVA) and safety profile. Results. Fourteen patients (19 eyes) were enrolled in the study. Scleritis inflammatory grading significantly improved from baseline to 3 months (p=0.002) and from baseline to the last follow-up visit (p=0.002). Scleritis relapses significantly decreased between the 12 months preceding and following biologic therapy (p=0.007). No differences regarding BCVA were observed (p=0.67). Regarding adverse events, only one patient developed pneumonia and septic shock under rituximab treatment. Conclusions. Our results, though limited to a low number of patients, highlight the effectiveness of different biologic therapies in the treatment of noninfectious refractory scleritis, showing to control scleral inflammation and allowing a significant reduction in the number of relapses.